Compensation System Attributes and Applicant Pool Characteristics - Williams, Margaret L.; Dreher, George F. (Academy of Management Journal, 1992)
The relationships between two compensation system attributes-pay level and the level and flexibility of benefits-and the number of applicants attracted to a job, the rate at which they accept the job, and the length of time it takes a firm to fill positions were examined using data on the process of hiring tellers from 352 U.S. banks. Pay level was positively related to acceptance rate as hypothesized, but was unrelated to the number of teller applicants. Opposite to prediction, pay level was positively related to the length of time it took banks to fill teller positions. Benefits were not related to acceptance rate; however, some aspects of benefit programs were positively related to both number of applicants and the time it took to fill positions, and some were negatively related. The study of relationships between human resource practices and firm performance and the implications of the findings for compensation strategy and practice are discussed.